2021
DOI: 10.1121/10.0006668
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the ultrasound attenuation and dispersion in 3D-printed photopolymer materials from 1 to 3.5 MHz

Abstract: Over the past decade, the range of applications in biomedical ultrasound exploiting 3D printing has rapidly expanded. For wavefront shaping specifically, 3D printing has enabled a diverse range of new, low-cost approaches for controlling acoustic fields. These methods rely on accurate knowledge of the bulk acoustic properties of the materials; however, to date, robust knowledge of these parameters is lacking for many materials that are commonly used. In this work, the acoustic properties of eight 3D-printed ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In another related study, by performing through-transmission measurements on 16 lmthick samples using air-coupled transducers in the frequency range of 0.15-0.35 MHz, Fariñas et al (2016) reported values of 1.9 and 2.8 MRayl for the acoustic impedances of TB þ and VW þ , respectively. In a recent study closely related to ours, by carrying out transmission measurements on a waterimmersed 4 mm-thick sample using a focused single-element transducer in the frequency range of 1-3.5 MHz, Bakaric et al (2021) reported values of around 2.50 mm/ls and 9 dB/cm for the frequency-dependent phase velocity and attenuation of VWþ, respectively. Extrapolating our modeling results to these frequencies yield (1) values of 2.43, 2.45, and 2.52 mm/ls for the phase velocity of VW þ at 1,2.25,and 20 MHz,respectively; (2) values of 8.1 and 104 dB/cm for the attenuation of VW þ at 2.25 and 20 MHz, respectively; and (3) values of 2.02 and 2.84 MRayl for the acoustic impedances of TB þ and VW þ at 0.25 MHz, respectively.…”
Section: Discussionsupporting
confidence: 60%
“…In another related study, by performing through-transmission measurements on 16 lmthick samples using air-coupled transducers in the frequency range of 0.15-0.35 MHz, Fariñas et al (2016) reported values of 1.9 and 2.8 MRayl for the acoustic impedances of TB þ and VW þ , respectively. In a recent study closely related to ours, by carrying out transmission measurements on a waterimmersed 4 mm-thick sample using a focused single-element transducer in the frequency range of 1-3.5 MHz, Bakaric et al (2021) reported values of around 2.50 mm/ls and 9 dB/cm for the frequency-dependent phase velocity and attenuation of VWþ, respectively. Extrapolating our modeling results to these frequencies yield (1) values of 2.43, 2.45, and 2.52 mm/ls for the phase velocity of VW þ at 1,2.25,and 20 MHz,respectively; (2) values of 8.1 and 104 dB/cm for the attenuation of VW þ at 2.25 and 20 MHz, respectively; and (3) values of 2.02 and 2.84 MRayl for the acoustic impedances of TB þ and VW þ at 0.25 MHz, respectively.…”
Section: Discussionsupporting
confidence: 60%
“…Specifically, the J835 prints 'primary' materials Agilus30 (rubber-like) and veroClear (Poly(methyl methacrylate)-like (PMMA)) and synthesises a broad range of 'derived' materials with mechanical properties varying between these two by depositing predetermined mixtures of the two primary materials. [29] In a recent work [30], the bulk acoustical properties of both of these primary materials as well as several of the derived materials (FLXA9960, FLXA9995, RGDA8625, and RGDA8630) were characterised, finding the group velocity between 1-3. While multi-polymer printing, in principle, offers sufficient fidelity and contrast its use introduces two additional challenges.…”
Section: Fabrication Requirementsmentioning
confidence: 99%
“…First, the losses due to attenuation within the photopolymers at 2 MHz range from 6.3-18 dB/cm. [30] Second, the sound speed distributions that can be fabricated are quantised. For simplicity, in this work, the design of holograms comprised of just 2 materials or binary distributions are considered.…”
Section: Fabrication Requirementsmentioning
confidence: 99%
“…More conveniently, v M ðxÞ and a M ðxÞ can also be expressed as a function of a reference frequency x c , where one can deliberately choose x c ¼ 2pf c (Bakaric et al, 2021), so that…”
Section: Mechanical Modeling a Szabo Wave Equationmentioning
confidence: 99%
“…Thereby, the achievement of complex materials and structures with specific acoustic responses relies on an accurate knowledge of the bulk acoustic properties of the elementary constituent materials. Within this context, a limited number of works have been carried out to report on the longitudinal bulk properties (i.e., phase velocity and attenuation) of photopolymer materials, as well as on their frequency dependence, by using different ultrasound methods, including a broadband reflection measurement technique using a focused single-element transducer (Jacquet et al, 2015;Jacquet et al, 2018), a two-sample substitution technique using a single-element broadband transducer as an emitter and a bilaminar hydrophone as a receiver (Bakaric et al, 2021), and a pulse-echo technique using a linear transducer array for launching and detecting a wideband plane wave (Aghaei et al, 2022). Although the reported longitudinal bulk properties are valuable towards ultrasound imaging and therapy purposes, emerging applications involving 3D-printed periodic micro-architectured media also require the knowledge of the transverse bulk properties to account for possible coupling mechanisms (Fielder and Nair, 2022;Kruisov a et al, 2018).…”
Section: Introductionmentioning
confidence: 99%